Streptococcus suis Serotype 2 Infection Impairs Interleukin-12 Production and the MHC-II-Restricted Antigen Presentation Capacity of Dendritic Cells - Letendre, Corinne; Auger, Jean-Philippe; Lemire, Paul; Galbas, Tristan; Gottschalk, Marcelo; Thibodeau, Jacques; Segura, Mariela (Frontiers in Immunology, 2018)
Streptococcus suis is an important swine pathogen and emerging zoonotic agent. Encapsulated strains of S. suis modulate dendritic cell (DC) functions, leading to poorly activated CD4+ T cells. However, the antigen presentation ability of S. suis-stimulated DCs has not been investigated yet. In this work, we aimed to characterize the antigen presentation profiles of S. suis-stimulated DCs, both in vitro and in vivo. Upon direct activation in vitro, S. suis-stimulated murine bone marrow-derived DCs preserved their antigen capture/processing capacities. However, they showed delayed kinetics of MHC-II expression compared to LPS-stimulated bmDCs. Meanwhile, splenic DCs from infected mice exhibited a compromised MHC-II expression, despite an appropriate expression of maturation markers. To identify potential interfering mechanisms, CIITA and MARCH1/8 transcription was studied. S. suis-stimulated DCs maintained low levels of Ciita at early time points, both in vitro and in vivo, which could limit their ability to increase MHC-II synthesis. S. suis-stimulated DCs also displayed sustained/upregulated levels of March1/8, thus possibly leading to MHC-II lysosomal degradation. The bacterial capsular polysaccharide played a partial role in this modulation. Finally, IL-12p70 production was inhibited in splenic DCs from infected mice, a profile compatible with DC indirect activation by pro-inflammatory compounds. Consequently, these cells induced lower levels of IL-2 and TNF- in an antigen-specific CD4+ T cell presentation assay and blunted T cell CD25 expression. It remains unclear at this stage whether these phenotypical and transcriptional modulations observed in response to S. suis in in vivo infections are part of a bacterial immune evasion strategy or rather a feature common to systemic inflammatory response-inducing agents. However, it appears that the MHC-II-restricted antigen presentation and Th1-polarizing cytokine production capacities of DCs are impaired during S. suis infection. This study highlights the potential consequences of inflammation on the type and magnitude of the immune response elicited by a pathogen.